Microstructure and microtexture evolutions of deformed oxide layers on a hot-rolled microalloyed steel. (January 2015) - Yu, Xianglong; Jiang, Zhengyi; Zhao, Jingwei; Wei, Dongbin; Zhou, Cunlong; Huang, Qingxue
Highlights: Microtexture development of deformed oxide layers is investigated. Magnetite shares the {0 0 1} fibre texture with wustite. Hematite develops the {0 0 0 1} basal fibre parallel to the oxide growth. Stress relief and ion vacancy diffusion mechanism for magnetite seam. Abstract: Electron backscatter diffraction (EBSD) analysis has been presented to investigate the microstructure and microtexture evolutions of deformed oxide scale formed on a microalloyed steel during hot rolling and accelerated cooling. Magnetite and wustite in oxide layers share a strong {0 0 1} and a weak {1 1 0} fibres texture parallel to the oxide growth. Trigonal hematite develops the {0 0 0 1} basal fibre parallel to the crystallographic plane {1 1 1} in magnetite. Taylor factor estimates have been conducted to elucidate the microtexture evolution. The fine-grained magnetite seam adjacent to the substrate is governed by stress relief and ions vacancy diffusion mechanism.